Advances in plant essential oils and drug delivery systems for skincare - Yihan, Wang; Jinjin, Dou; Yingqi, Wang; Guanai, Mu; Xiwu, Zhang (Frontiers in Pharmacology, 2025)
BackgroundEssential oils, often referred to as “liquid gold,” are renowned for their broad biological activity. Ancient Egyptians used essential oils’ antibacterial and antiseptic effects to preserve mummies, ancient Greeks used olive oil for sun protection, and ancient Chinese used essential oils to treat wounds. When essential oils are applied to the facial skin, their potent anti-inflammatory, antioxidant, and antibacterial pharmacological characteristics provide various benefits, including sunscreen, skin-whitening, and anti-aging effects.PurposeThis paper aims to summarize the application of plant essential oil in skin whitening, anti-inflammatory, antioxidant and antibacterial in recent years, and deeply analyzes the internal relationship between essential oil and modern drug delivery system, expounds how to overcome the limitations of essential oil through specific drug delivery system, to enhance its biological activity and stability, realize sustained release and reduce its potential toxicity, and also discusses the positive effects of essential oil on brain function through olfactory pathway, emphasizes the possible safety risks in the use of essential oil, and puts forward corresponding suggestions for use.MethodsUsing keywords such as “essential oils,” “antioxidant,” “anti-tyrosinase,” Antibacterial Effects and anti-inflammatory,” “anti-anxiety,” and “drug carrier delivery systems,” a comprehensive search was conducted in the PubMed, CNKI, Baidu, and Wanfang databases to summarize articles from the past 5 years. Further screening was performed to select studies demonstrating the efficacy of essential oils through topical or external application.ResultsVarious essential oils showed their efficacy as strong oxidants, antibacterial agents, anti-inflammatory agents, and skin-whitening agents. Combined with a new drug delivery system, it not only enhances the biological activity of essential oil but also reduces the inherent defects of essential oil, such as volatility, irritation, and toxicity, and has a targeted delivery effect. At the same time, the integration of essential oil into skin care products can make use of the dual functions of smell and the epidermal system to nourish and repair the skin and maximize the pharmacological effects of essential oil.ConclusionThis review delves into the application of essential oils and delivery systems, advocating for a broader integration of natural plant resources with modern technology. By strategically utilizing essential oils, we can promote the sustainable development of the global economy. However, extensive clinical trials are still required to evaluate the effectiveness and safety of essential oil delivery systems.